Karakteristik Edible film dari Pati Umbi Garut (Maranta arundinacea) dengan Penambahan Carboxymethylcellulose Batang Jagung (Zea mays) - afriyanti afriyanti; novian wely asmoro; retno widyastuti (Universitas Veteran Bangun Nusantara, 2021)
One of the main ingredients in making edible films is starch. Arrowroot has a high starch content so that it can be used as raw material for making edible films. To increase the tensile strength and improve the surface structure of the edible film, it is necessary to add carboxymethylcellulose (CMC). However, it is necessary to have the right CMC concentration in order to produce an edible filmwith optimal tensile strength. The purpose of this study was to determine the correct CMC concentration of corn stalks to produce edible films with the best physical and chemical characteristics. The experimental design used in this study was a non-factorial completely randomized design, namely the concentration of commercial CMC: CMC corn stalks (ml) with five treatment levels, namely: A1 = 1: 0; A2 = 0.75: 0.25; A3 = 0.5: 0.5; A4 = 0.25: 0.75; and A5 = 0: 1. Each treatment was repeated four times in order to obtain the experimental unit 5 x 4 = 20 experimental units. The product analysis carried out was the moisture content, thickness, and pH of the edible film. The data obtained were calculated statistically with Anova and if there was a significant difference between treatments, it was continued with the Duncan's Multiple Range Test (DMRT). The highest water content and thickness were obtained in the addition of 1 ml (A) CMC treatment.Keywords: arrowroot, carboxymethylcellulose, corn, edible film